Antibacterial Combination of Oleoresin from Copaifera multijuga Hayne and Biogenic Silver Nanoparticles Towards Streptococcus agalactiae - S. Otaguiri, Eliane; E.B. Morguette, Ana; P. Biasi-Garbin, Renata; T. Morey, Alexandre; A.C. Lancheros, Cesar; Kian, Danielle; G. de Oliveira, Admilton; Kerbauy, Gilselena; R.E. Perugini, Marcia; Duran, Nelson; V. Nakamura, Celso; F. da Veiga, Valdir; et al. (Current Pharmaceutical Biotechnology, 2017)
Background: Streptococcus agalactiae (group B Streptococcus - GBS) remains a leading cause of neonatal infections and an important cause of invasive infections in adults with underlying conditions. Methods: This study evaluated for the first time the effect of an oleoresin collected from Copaifera multijuga Hayne (copaiba oil) alone or in combination with silver nanoparticles produced by green synthesis using Fusarium oxysporum (AgNPbio) against planktonic and sessile cells of GBS isolated from colonized women. Results: Copaiba oil showed a dose-dependent bactericidal activity against planktonic GBS strains, including those resistant to erythromycin and/or clindamycin. Scanning and transmission electron microscopy of GBS treated with copaiba oil revealed morphological and ultrastructural alterations, displaying disruption of the cell wall and decreased electron density due to leakage of cytoplasmic content. Copaiba oil also exhibited antibacterial activity against biofilms of GBS strains, inhibiting their formation as well as the viability of mature biofilms. In addition, the combination of copaiba oil with AgNPbio resulted in a synergistic effect against planktonic cells and biofilm formation, reducing the minimal inhibitory concentration values of both compounds. No hemolytic activity was detected for both compounds. Conclusion: These results indicate the potential of copaiba oil, alone or in combination with AgNPbio, for the development of new alternative strategies for controlling GBS infections.
Keywords: biological silver nanoparticles